Lignin-derived carbon nanosheets boost electrochemical reductive amination of pyruvate to alanine - Shunhan Jia; Xingxing Tan; Limin Wu; Ziwei Zhao; Xinning Song; Jiaqi Feng; Libing Zhang; Xiaodong Ma; Zhanrong Zhang; Xiaofu Sun; Buxing Han (iScience, 2023)
Summary: Efficient and sustainable amino acid synthesis is essential for industrial applications. Electrocatalytic reductive amination has emerged as a promising method, but challenges such as undesired side reactions and low efficiency persist. Herein, we demonstrated a lignin-derived catalyst for alanine synthesis. Carbon nanosheets (CNSs) were synthesized from lignin via a template-assisted method and doped with nitrogen and sulfur to boost reductive amination and suppress side reactions. The resulting N,S-co-doped carbon nanosheets (NS-CNSs) exhibited outstanding electrochemical performance. It achieved a maximum alanine Faradaic efficiency of 79.5%, and a yield exceeding 1,199 μmol h−1 cm−2 on NS-CNS, with a selectivity above 99.9%. NS-CNS showed excellent durability during long-term electrolysis. Kinetic studies including control experiments and theoretical calculations provided further insights into the reaction pathway. Moreover, NS-CNS catalysts demonstrated potential in upgrading real-world polylactic acid plastic waste, yielding value-added alanine with a selectivity over 75%.